Gonadal function after allogenic bone marrow transplantation for thalassaemia. Issue 4 (April 1991) - De Sanctis, V; Galimberti, M; Lucarelli, G; Polchi, P; Ruggiero, L; Vullo, C
Abstract : Thirty prepubertal patients with thalassaemia major (15 boys and 15 girls) aged from 9.3 to 17.2 years (mean 12.9) who had successfully undergone allogenic bone marrow transplantation were studied. Before the transplant all patients were given short courses of high doses of busulphan (total dose 14 mg/kg) followed by cyclophosphamide (total dose 200 mg/kg). Pituitary gonadal function was assessed between 0.7 and 5.1 years (mean 2.3) after bone marrow transplantation. Increased gonadotrophin concentrations indicating gonadal damage were found in 80% of the girls, probably as a result of the chemotherapy. In all the prepubertal boys the basal follicle stimulating hormone and luteinising hormone concentrations were normal. Most of the boys had reduced gonadotrophin and testosterone responses after gonadotrophin releasing hormone and human chorionic gonadotrophin tests. This could have been the result of iron overload but the effect of cytotoxic agents cannot be excluded. These findings emphasise the need for vigilant long term follow up of thalassaemic patients treated with cytotoxic chemotherapy for bone marrow transplantation so that those requiring hormone replacement can be identified and treated.